A Comparative Study on Self Perceived Health and Quality of Life of Parents of Children with Autism Spectrum Disorders and Parents of Non Disabled Children in Croatia - Benjak, Tomislav; Mavrinac, Gorka Vuletić; Šimetin, Ivana Pavić; Kolarić, Branko (IntechOpen, 2011)
None